Bulleyaconitine A reduces fracture-induced pain and promotes fracture healing in mice - Peng, Jun; Xiao, Sheng; Xie, Juan; Fu, Wan (Frontiers in Pharmacology, 2023)
A fracture is a severe trauma that causes dramatic pain. Appropriate fracture pain management not only improves the patient's subjective perception, but also increases compliance with rehabilitation training. However, current analgesics for fracture pain are unsatisfactory because of their negative effects on fracture healing or addiction problems. Bulleyaconitine A (BLA), a non-addictive analgesic medicine, is used for the treatment of chronic pain of musculoskeletal disorders in clinical practice, whereas the effects of BLA on fracture pain is undefined. To evaluate the analgesic effects of BLA on fracture, we generated tibial fracture mice here. It is found that oral administration of BLA to mice alleviates fracture-induced mechanical and thermal hyperalgesia. Interestingly, BLA significantly increases locomotor activity levels and reduces anxiety-like behaviors in fractured mice, as determined by open-field test. Notably, BLA treatment promotes bone mineralization and therefore fracture healing in mice, which may be attributed to the increase in mechanical stimulation caused by exercise. Our study suggests that BLA can be used as a promising analgesic agent for the treatment of fracture pain.